The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/13504851.2020.1851643
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic news and stock market reaction during the onset of the crisis: evidence from high-frequency data

Abstract: Using 30-minute tick returns, we examine the impact of changes in the number of COVID-19 news on eight different stock markets during the initial two months of the coronavirus crisis 2020. We do not find evidence that stock returns are sensitive to the changes in the number of COVID-19 news. However, there is strong evidence that changes in COVID-19 news increase stock market volatility in European markets. The findings also suggest that a substantial part of market uncertainty can be explained by changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 8 publications
3
53
0
1
Order By: Relevance
“…We present a main hypothesis that the large-scale COVID-19 pandemic provokes investor sentiment, and particularly a rise in fear and anxiety, which in turn negatively impacts stock prices. Accordingly, we observe that the media coverage ( Ambros et al., 2020 ) which spreads information about the pandemic, generating fear and anxiety and even conveying fake news ( Brigida and Pratt, 2017 ), increases the level of pessimistic attitudes towards investment decisions ( Da et al., 2015 ). We structure the mechanism of sentiment and equity markets in three main pillars, which are relevant to our indicators:…”
Section: Literature Reviewmentioning
confidence: 94%
“…We present a main hypothesis that the large-scale COVID-19 pandemic provokes investor sentiment, and particularly a rise in fear and anxiety, which in turn negatively impacts stock prices. Accordingly, we observe that the media coverage ( Ambros et al., 2020 ) which spreads information about the pandemic, generating fear and anxiety and even conveying fake news ( Brigida and Pratt, 2017 ), increases the level of pessimistic attitudes towards investment decisions ( Da et al., 2015 ). We structure the mechanism of sentiment and equity markets in three main pillars, which are relevant to our indicators:…”
Section: Literature Reviewmentioning
confidence: 94%
“…When it comes to the comparison between COVID-19 event and other public health crises, Schell et al (2020) indicated that the coronavirus outbreak exhibits the significant negative abnormal returns across the majority of equity markets while this phenomenon does not exist in the remaining events such as Ebola, Zika virus, and so forth. In the same vein, the study of Ambros et al (2020) investigates the role of news on the stock markets returns and volatility. Although this paper sheds a new light on null results of potential channel between returns and pandemic news, the aforementioned paper provides an empirical evidence about the role of number of disease news significantly the European market volatility.…”
Section: Brief Literature Review Regarding Covid-19 Impacts On Financial Marketsmentioning
confidence: 99%
“…On that day, the Shanghai Composite Index fell by 2.75% and the Shenzhen Component Index fell by 3.52%. Therefore, this paper selects January 23, 2020 as the first day of the impact of the new epidemic on all industries in the securities market ( Ambros et al., 2020 ; Schell et al., 2020 ). As a result, all data before January 23, 2020 are used for the control group and all data after January 23 are used for the treatment group.…”
Section: Data and Empirical Analysismentioning
confidence: 99%